Protocol for a systematic review and meta-analysis assessing the effectiveness of deprescribing in falls prevention in older people - Olive Kobusingye; Kenneth Madden; Jesper Ryg; Gustavo Duque; Leilei Duan; Ian Cameron; Clemens Becker; Chris Todd; Pip Logan; Nathalie van der Velde; Sirpa Hartikainen; Alice Nieuwboer; et al. (BMJ Open, 2021)
Introduction One of the known risk factors for fall incidents is the use of specific medications, fall-risk-increasing drugs (FRIDs). However, to date, there is uncertainty related to the effectiveness of deprescribing as a single intervention in falls prevention. Thus, a comprehensive update of the literature focusing on all settings in which older people receive healthcare and all deprescribing interventions is warranted to enhance the current knowledge.Methods and analysis This systematic review protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic search was performed in Cochrane Central Register of Controlled Trials, MEDLINE, Embase and PsycINFO (2 November 2020). We will also search in trial registers. We will include randomised controlled trials, in which any deprescribing intervention is compared with usual care and reports falls as an outcome. Both title and abstract screening and full-text screening will be done by two reviewers. The Cochrane Collaboration revised tool of Risk of Bias will be applied to perform risk of bias assessment. We will categorise the results separately for every setting. If a group of sufficiently comparable studies will be identified, we will perform a meta-analysis applying random effects model. We will investigate heterogeneity using a combination of visual inspection of the forest plot along with consideration of the χ2 test and the I2 statistic results. We have prespecified several subgroup and sensitivity analyses.Ethics and dissemination Ethics approval is not applicable for this study since no original data will be collected. The results will be disseminated through peer-reviewed publication and conference presentations. Furthermore, this systematic review will inform the recommendations of working group of polypharmacy and FRIDs of the anticipated World’s Falls Guidelines.PROSPERO registration number CRD42020218231.